Pengaruh Literasi Keuangan, Literasi Akuntansi, dan Literasi Digital terhadap Kinerja UMKM Subsektor Usaha Mikro di Kota Pontianak Tahun 2022 - jahuri, siti nurhasanah (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study evaluates the revenue and expenditure performance of the Pontianak City Government during the 2018–2022 period. The study employs a descriptive method with a quantitative approach using secondary data obtained from the Directorate General of Fiscal Balance. Regional revenue performance was analyzed through revenue variance, revenue growth, degree of decentralization, regional financial independence, and revenue effectiveness. Regional expenditure performance was analyzed through expenditure variance, expenditure growth, expenditure compatibility, and expenditure efficiency. The results show that regional revenue variance was generally categorized as unfavorable, while revenue growth was predominantly positive. The average degree of decentralization was 28%, indicating a moderate level, whereas regional financial independence averaged 48%, indicating a low level with a consultative relationship pattern. Regional revenue effectiveness averaged 94% and was categorized as effective. Regional expenditure variance was categorized as favorable, while expenditure growth was predominantly positive. Operating expenditure accounted for an average of 73% of total expenditure and was categorized as compatible, whereas capital expenditure accounted for an average of 27% and was categorized as less compatible. Regional expenditure efficiency averaged 92% and was categorized as less efficient.